As Wide as the Roots of the Olive Tree: Indigenous Communities of Masafer Yatta and their Eco-Resistance - Stagni, Federica (PARTECIPAZIONE E CONFLITTO, 2024)
In Palestine, the eradication of the Indigenous population extends beyond physical displacement and destruction; it entails ecological transformations. Analogous to other settler-colonial contexts, nature is not merely annihilated; rather, it is molded to suit the colonizer's intentions, resulting in modification. This article examines the eco-resistance by the Indigenous people of Masafer Yatta as an Indigenous response to the environmental impact of the Israeli neocolonial entity. By delineating the tactics employed by settlers in the region to erase the Indigenous presence, the article aims to provide a comprehensive analysis of colonial dominance over Indigenous lives and knowledge across multiple scales. This analysis is grounded in extensive field immersion spanning from 2016 to 2022. The article addresses critical questions: How does Indigenous resistance manifest in the Masafer Yatta region? What strategies have Israeli settlers implemented on the ground to supplant the Indigenous population in the area? How does settler colonial dominance intersect with macro-economic dimensions and policies? While these questions have been explored within Palestine Studies scholarship and literature, this analysis is distinctive in its reliance on the specific case of Masafer Yatta. This area has received limited scholarly attention to date.